Swarm, Evolutionary, and Memetic Computing 4th International Conference, SEMCCO 2013, Chennai, India, December 19-21, 2013, Proceedings, Part II - Panigrahi, Bijaya Ketan; Suganthan, Ponnuthurai Nagaratnam; Das, Swagatam; Dash, Shubhransu Sekhar (Theoretical Computer Science and General Issues, 2013)
The two-volume set LNCS 8297 and LNCS 8298 constitutes the proceedings of the 4th International Conference on Swarm, Evolutionary and Memetic Computing, SEMCCO 2013, held in Chennai, India, in December 2013. The total of 123 papers presented in this volume was carefully reviewed and selected for inclusion in the proceedings. They cover cutting-edge research on swarm, evolutionary and memetic computing, neural and fuzzy computing and its application.